EBario map-based tourism website - Fung, Yuen Wui; Loh, Chee Wyai; Ong, Siou Chin; Su, Chee Hoi (University Malaysia Sarawak, (UNIMAS), 2004)
This map-based Bario tourism website is part of the eBario research project. It is developed to promote tourism in Bario and to preserve its cultural heritage. The website contains information about Bario and the Kelabits. In addition, users may make accommodation and tourist guide reservation through the website. The website also consists of a zoom-able map that is built using Scalable Vector Graphic (SVG) format.